Retrospective, multicenter analysis comparing conventional with oncoplastic breast conserving surgery: oncological and surgical outcomes in women with high-risk breast cancer from the OPBC-01/iTOP2 study - Fitzal, Florian; Bolliger, Michael; Dunkler, Daniela; Geroldinger, Angelika; Gambone, Luca; Heil, Jörg; Riedel, Fabian; de Boniface, Jana; Andre, Camilla; Matrai, Zoltan; Pukancsik, Dávid; Paulinelli, Regis R.; et al. (Annals of surgical oncology, 2022)
Recent data suggest that margins ≥2 mm after breast-conserving surgery may improve local control in invasive breast cancer (BC). By allowing large resection volumes, oncoplastic breast-conserving surgery (OBCII; Clough level II/Tübingen 5-6) may achieve better local control than conventional breast conserving surgery (BCS; Tübingen 1-2) or oncoplastic breast conservation with low resection volumes (OBCI; Clough level I/Tübingen 3-4)